Al-Alʿāb al-Iliktrūniyyah wa Ḥukm Mumārasatihā fī Manẓūr al-Fatāwā al-Islāmiyyah - Humaira, Aida; Hidayati, Alfi Laela; Rahman, Muh. Fudhail (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
Islamic law permits Muslims to engage in activities that bring them enjoyment, such as playing online games. However, this is subject to the rules and regulations established by Sharia, which aim to ensure that all aspects of a Muslim's life adhere to Islamic principles and do not violate them. This research aims to analyze the ruling on playing electronic games according to Islamic fatwas, taking into account the impact of technological developments on Islamic societies. The study addresses scholars' opinions on the legal aspects of online games, including conditions for permissibility and prohibitions, as well as potential risks and benefits. An analytical approach was used, wherein research describes the ruling on gaming in Islam and analyzes data from jurisprudential sources, the Quran, and Hadith literature. The findings indicate that the basic ruling on playing online games is permissibility, provided it is not associated with any legal violations and does not lead to any harmful consequences. This permissibility may extend to other legal rulings based on the relevant context; however, it pertains to two matters: the contents of the game and its outcomes, such as player behavior and the resulting effects.